Holistic English Mid-Term Assessment for Junior High Schools - RestiMartanti, Ika Fathin (Indonesian Journal of English Language Studies (IJELS), 2015)
Assessment is one of integrated parts in teaching and learning process. Due to the change of curriculum in Indonesia, the assessment type which the teachers should use to assess theirstudents is different. According to Curriculum 2013, teachers need to assess every studentthoroughly, including their knowledge, skills, and attitudes. In fact, teachers still finddifficulties in assessing their students. This phenomenon also happens to the teachers ofjunior high schools. This research aims to develop a mid-semester assessment model which ismore practical and less time-consuming for English teachers in junior high schools. Themethod was Research and Development (R&D). The data were collected from groupdiscussion, questionnaires, and interviews. The result of the research is a holistic Englishassessment model which can be used for a mid-semester period. A holistic assessment coversthe partial and contextual aspects of teaching and learning. It consists of two types: studentassessment and portfolio assessment. This assessment model is expected to improve theeffectiveness of the assessment technique for junior high schools and to provide moreopportunities for teachers to conduct the mid-term assessment which is not really taken intoaccount as a part of classroom activities. Keywords: assessment, holistic, mid-semester, junior high school